2018
DOI: 10.12659/msm.909350
|View full text |Cite
|
Sign up to set email alerts
|

Keratin 17 Promotes Lung Adenocarcinoma Progression by Enhancing Cell Proliferation and Invasion

Abstract: BackgroundsLung adenocarcinoma (LAC) accounts for the majority of lung cancer, which is the leading cause of cancer-related mortality worldwide. Keratin 17 (KRT17) was reported to promote the tumor development of skin tumor and oral cancer. The aim of this study was to investigate the expression and function of KRT17 in LAC.Material/MethodsImmunohistochemical staining and quantitative PCR were performed to explore the expression of KRT17 in both LAC tissues and adjacent normal liver tissues. Chi-square test, u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 34 publications
1
37
0
Order By: Relevance
“…Of note, LAC and SCC account for 50% and 30%, respectively (Larrayoz et al, ). Despite the remarkable advances in diagnosis and therapeutic technology, the 5‐year survival rate for NSCLC patients is still approximately 15% (Miller, ; Liu et al, ; Men et al, ). Therefore, better understanding of the cellular and molecular changes in lung cancer is essential.…”
Section: Introductionmentioning
confidence: 99%
“…Of note, LAC and SCC account for 50% and 30%, respectively (Larrayoz et al, ). Despite the remarkable advances in diagnosis and therapeutic technology, the 5‐year survival rate for NSCLC patients is still approximately 15% (Miller, ; Liu et al, ; Men et al, ). Therefore, better understanding of the cellular and molecular changes in lung cancer is essential.…”
Section: Introductionmentioning
confidence: 99%
“…4C, bottom); for example, NFKBIA (IκBα) is a pan-cancer tumor 20 suppressor via inhibition of pro-tumoral NFκB signaling (54), overexpression of ID3 inhibits tumor cell migration and invasion in vitro and in similar xenograft models of lung adenocarcinoma xenograft (55), and downregulation of ASS1 supports tumor metabolism and proliferation (56). Paradoxically, our most significant negative hit is KRT17, which has previously been implicated in promoting invasiveness in lung adenocarcinoma (57) and its overexpression is associated with poor prognosis in many cancers (58). This suggests that KRT17 may play a context-specific role in metastatic progression in this model, which could be further explored experimentally.…”
Section: Transcriptional Signatures Of Distinct Metastatic Phenotypesmentioning
confidence: 77%
“…According to Balabko et al (2014) RORC is a specific transcription factor in the tumor area of lung tissue in patients with LUAD. DLX5 (Kato et al, 2008;Balabko et al, 2014), MUC1 (Mashima et al, 2005;Molina-Pinelo et al, 2014), and KRT17 (Erdogan et al, 2009;Liu et al, 2018) were found to be overexpressed in LUAD.…”
Section: The Biological Significance Of the Identified Signaturementioning
confidence: 94%